The use of the Jewish scripture in the Johannine Passion narrative that the scripture may be perfected - Allen, David M. 1972- (Lexington Books, 2024)
"This book examines the use of Israel's Scriptures in the Fourth Gospel's account of Jesus' death. It pays particular attention to John's concept of scriptural fulfilment, and particularly the accompanying "perfection" of Scripture in this regard; for John, the status of the Jewish Scriptures is enhanced by Christ's Passion."
Includes bibliographical references and index
Keywords: Passion Jesu; Bibel -- Altes Testament; Bibel -- Johannesevangelium -- 18,1-19,42; Rezeption; Jesus Christ / Passion; Bible / John / Criticism, interpretation, etc; Bible / Old Testament / Quotations in the New Testament; Bible / John / Relation to the Old Testament